Integrating digitization into public administration: Impact on national security and the economy through spatial planning - Sydorchuk, Orystlava; Bashtannyk, Vitalii; Terkhanov, Fedir; Kravtsov, Oleg; Akimova, Liudmуla; Akimov, Oleksandr (Edelweiss Applied Science and Technology, 2024)
The evolutionary development of the security sphere, on the one hand, and the rapid involvement of digital technologies (and, as a consequence, changes) on the other, formulate the first level of problematization of this study. The study seeks to provide evidence of how the dynamics of changes in the security sphere are formed by constructing an empirical model of changes and assessing the state security system within the framework of spatial planning under the influence of digital technologies. Particular attention in the study is paid to spatial planning and spatial development in smart cities the main threats to national security are systematized, located in closely intersecting planes of digital technologies, social processes, and economic interests. It is shown that areas covered by spatial planning, and particularly smart cities, pose a serious local threat to national and international security policy at the levels of political, social, technical, and economic governance.